Follow the leader: testing a deductive approach for studying parliamentary party leadership roles. Issue 3 (3rd July 2018) - de Vet, Benjamin; Wauters, Bram
ABSTRACT: Parliamentary party group leaders (PPG leaders) are crucial – yet understudied – actors in modern representative democracies. Inspired by the literature on parliamentary roles, we test a deductive approach in order to explore the attitudes and behaviours of PPG leaders. Given their common duties, such as monitoring group members and securing party cohesion, we expect that PPG leaders across several countries would exhibit a common pattern that distinguishes them from other MPs. However, neither a common, nor a distinguished pattern of attitudes and behaviour is confirmed by our results based on Partirep MP Survey data. This, together with other theoretical difficulties, points us to the need to study PPG leaders' roles by using in-depth single-country studies.